Rigid plastic plates at large deformations - Vu Van The (Vietnam Journal of Mechanics)
By being statically loaded plastic plates can support loads exceeding the bending collapse pressure, the behaviour of perfectly rigid plastic plates beyond the yield load depends on changes in geometry to the plastic flow. Therefore in post yield behaviour the deflection can not be considered small in comparison with the plate thickness. In this paper we employ the equations of plates at moderately large deflections and the approximate live behaviour of plates introduced in/2,3/ by dividing plates into a number of rigid regions which have been separated by line hinges situated at locations where their discontinue ties in w,i occur, an estimative method of the toad - deflection relationship of arbitrarily shaped plates having arbitrarily boundary conditions is developed. This method is directly extended to anisotropic and reinforced concrete plates.